A formação itinerante : experiências e percepções de professores iniciantes do OBEDUC/UFMT - Souza, Dulcinete Rodrigues dos Santos Alves de (2019)
This study approaches the education of beginner teachers from the public schools in Rondonópolis-MT developed by the research group called InvestigAtion (InvestigAção), in a collaborative Project University/UFMT – School, which invests in the itinerancy at and through the schools investigating the dilemmas, challenges and potentialities of the teachers in the first years of teaching. In this scenario, it was objectified to investigate that difficulties, dilemmas and training needs show the beginner teachers and what potential they present to overcome this picture from a formation and practice shared with their peers, in a propitious space of alterity in the roaming of the schools involved.It was also analysed how teachers comprehend and acquire this education to diminish their impasses when dealing with their own practices on the Science teaching and follow the peculiarities showed in each locus from the experience got among them. The itinerancy made the beginner teachers share knowledge, metodologies, practices, knowings and doings from this part of the teaching, in different realities, being aware every education happened at a school. Using the qualitative approach and the formative research, we intend to answer the following questions: What are the dilemmas and potentialities of beginning teachers? Does the process of experiencing itinerancy contribute to understanding these dilemmas, reducing afflictions and developing their potential?What do the Science Teachers manifest about the possibilities of giving a new meaning to their knowledge and practices from the education offered? The production of data came from documental analysis and narratives from different instruments including the online ones. The results showed the continuing education offered by the OBEDUC/UFMT Project is considered by the teachers as a point to reflect about their practices and their teaching career, contributing, therefore, to their professional development. The itinerancy suggested during the education brought to the teachers a possibility to review the practices of one another and resulted in an instrument to improve and probably promote alterity, helping to decrease the difficulties and fill their initial education gaps.